Total quality process control for injection molding [ - Gordon, M. Joseph (Wiley series in plastics engineering and technology, 2010)
"This book provides the guidance and information to manufacture plastic parts "right the first time" and continue this process through all manufacturing operations. The book explores, in detail, different ways to improve plastics part design and quality, processabilty,and total manufacturing. Also included are material and process control procedures with control charting in "real time" to monitor quality through the entire manufacturing system. Problem analysis techniques and troubleshooting procedures are presented to improve a company's process control system and solve manufacturing problems"-- Provided by publisher